2020
DOI: 10.1002/ijc.33131
|View full text |Cite
|
Sign up to set email alerts
|

Genetically driven CD39 expression shapes human tumor‐infiltrating CD8+ T‐cell functions

Abstract: In our study, we investigated the role of CD39 on tumor‐infiltrating CD8+ T lymphocytes (CD8+ TILs) in colorectal, head and neck and pancreatic cancers. Partially confirming recent observations correlating the CD39 expression with T‐cell exhaustion, we demonstrated a divergent functional activity in CD39+CD8+ TILs. On the one hand, CD39+CD8+ TILs (as compared to their CD39− counterparts) produced significantly lower IFN‐γ and IL‐2 amounts, expressed higher PD‐1, and inversely correlated with perforin and granz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 47 publications
1
31
0
Order By: Relevance
“…Most data described a strong correlation between elevated CD73 levels and unfavorable clinical outcomes, as was observed for CD39 [ 36 , 37 , 38 , 39 ]. Through CD39 and CD73 blockade, likely limiting the conversion of ATP/AMP into adenosine, many mouse, human and in vitro studies showed inhibition of both tumor growth and metastasis formation, generally associated with an increase of NK and/or CD8 T cell immune-mediated antitumor responses [ 21 , 25 , 33 , 40 , 41 , 42 , 43 , 44 ].…”
Section: Adenosine Pathway and Cd39/cd73 Expression In The Tumor Microenvironmentmentioning
confidence: 99%
“…Most data described a strong correlation between elevated CD73 levels and unfavorable clinical outcomes, as was observed for CD39 [ 36 , 37 , 38 , 39 ]. Through CD39 and CD73 blockade, likely limiting the conversion of ATP/AMP into adenosine, many mouse, human and in vitro studies showed inhibition of both tumor growth and metastasis formation, generally associated with an increase of NK and/or CD8 T cell immune-mediated antitumor responses [ 21 , 25 , 33 , 40 , 41 , 42 , 43 , 44 ].…”
Section: Adenosine Pathway and Cd39/cd73 Expression In The Tumor Microenvironmentmentioning
confidence: 99%
“…ATP hydrolysis drives the immune response to collaborate with tumor growth, making the CD39/CD73 axis an important regulator of immune effector function. This is a hallmark of cancer ( 78 81 ). Interestingly, CD39 inhibition can restore TIL function, and a single nucleotide polymorphism has been identified that may predict dysfunctional CD39 + expression in TILs in some solid tumors ( 81 ).…”
Section: Immune System In Gliomasmentioning
confidence: 99%
“…Simoni et al found that CD39 may be a predictive biomarker for patients to respond to CD8 + TIL targeted cancer immunotherapy. Whether CD8+ TIL cells express CD39 or can predict the response degree of patients to PD-1 antibody therapy, it is of great help to screen more potential anticancer T cells in TIL and CAR-T cell therapy, and further expand the immunotherapy (80)(81)(82).…”
Section: Cd39mentioning
confidence: 99%